A Retrospective Study On The Association Of Prior Low Dose Aspirin Therapy Diabetics With Helicobacter Pylori Infection - Arief Hamid; Mohamad Fairuz Mohamad Sharin (Heirourgike Etaireia Boreiou Ellados SURGICAL SO, 2024)
Helicobacter pylori is one of the most common bacterial infection in the world causing a significant impact on public health. The infection is usually asymptomatic, but when symptom arises, it is commonly tested for via endoscopy and the CLO (Campylobacter Like Organism) test. Due to the majority of patients being asymptomatic and a variable time frames of presentation, studying and establishing a temporal relationship between H. pylori and predisposing factors can be very challenging. Previous studies have shown that H. pylori infection is more prevalent among diabetic patients. Aspirin is now more commonly used in the prophylactic management of diabetic patients and is also known to be associated with gastric mucosal damage. This retrospective study investigates any association of Low Dose Aspirin (LDA) therapy in diabetics with H. pylori infection. The study involves endoscopic records of 274 diabetic patients who received and without LDA respectively, and analysis showed there is an association between LDA therapy in diabetics with H pylori infection, whereby LDA group had a lower H. pylori infection (n=0.02).